Case Report: A Rare Case of Thrombotic Microangiopathy Induced by Remethylation Disorders - Pang, Lu; Chen, Jian; Yu, Haiyan; Huang, Haiming; Jin, Bo; Wang, Xin; Li, Haixia (Frontiers in Medicine, 2022)
In this research, we described a very rare case of thrombotic microangiopathy induced by remethylation disorders. A 16-year-old boy presented to the emergency department with 5 months of weakness and fatigue. He was diagnosed as thrombotic microangiopathy based on clinical manifestation and laboratory information, which showed microangiopathic hemolytic anemia, renal impairment and thrombocytopenia. After a complex diagnostic workup, the metabolite screening parameters and sequencing results guided us toward the diagnosis of remethylation disorders. The patient was diagnosed as thrombotic microangiopathy induced by remethylation disorders (cblC).